Kinetics and Mechanism of Oxidation of Ethylenediamine by Chromic acid in Perchloric Acid Medium - Gupta, Sangeeta; Seth, G.K. (Asian Journal of Chemistry, 2010)
Kinetic studies on oxidation of ethylenediamine by chromic acid in the presence of perchloric acid have been made. The results indicate first order kinetics with respect to each chromic acid, ethylenediamine and [H+]. Insignificant effect of ionic strength of the medium has been observed. Increase in chromic acid was found to show retarding effect on reaction rate. A suitable mechanism on the basis of kinetic results has been proposed.